Quakers Living in the Lion's Mouth : The Society of Friends in Northern Virginia, 1730-1865 - Crothers, A. Glenn (Book collections on Project MUSE., 2012)
This examination of a Quaker community in northern Virginia, between its first settlement in 1730 and the end of the Civil War, explores how an antislavery, pacifist, and equalitarian religious minority maintained its ideals and campaigned for social justice in a society that violated those values on a daily basis. By tracing the evolution of white Virginians' attitudes toward the Quaker community, Glenn Crothers exposes the increasing hostility Quakers faced as the sectional crisis deepened, revealing how a border region like northern Virginia looked increasingly to the Deep South for its cult.